SOCIAL MEDIA AND FAMILY DIVORCES - Reza Fahmi (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2019)
As a Facebook friendship site it is often misused as a case; spread hoax news , deliver hate speech and so on. Furthermore, the purpose of this study are: (1) To get an idea of the characteristics of Facebook social media users in the middle class in the city of Padang. (2) Obtaining a picture of divorce that occurs in the middle class society in the city of Padang. (3) Proving the relationship between the use of Facebook and divorce in middle class families in the city of Padang. The population in the study was 368 people. While the study sample was 191 people. This study uses a quantitative descriptiveapproach . The technique of collecting data through psychological scales and interviews. Sampling technique using simple random sampling . Data analysis techniques using the Pearson correlation. The results of the study found that r count = 3.86 <r table 5.92, which means there is no relationship between the use of facebook and divorce in the family in the middle social class in the city of Padang.